LEGAL PROTECTION FOR BORN BABIES FROM THE ECTOLIFE PROGRAM - Indri Hapsari; Sutarno; Andika Persada Putera (JILPR Journal Indonesia Law and Policy Review, 2023)
This research aims to analyze the legal protection of babies born from the EctoLife program and its ethical aspects. The research method used is a normative juridical research method with a statutory and conceptual approach. The data collection technique used is by means of literature research. The results showed that the EctoLife baby program according to positive law in Indonesia does not yet exist because the research is also only conducted in the trial stage on animals with partial ectogenesis design. EctoLife Bioethically prohibited both internationally and in Indonesia due to the prohibition of growing embryos longer than 14 days and the prohibition on selecting gender, skin color and other traits for genetic engineering other than for medical purposes.